Regulacyjna funkcja intuicji językowej w rozwijaniu podsystemu leksykalno-semantycznego: test wnioskowania znaczeń w limitowanym czasie - Piegzik, Wioletta A. (Neofilolog, 2021)
The paper emphasizes the role of linguistic intuition in current L2 processing. Intuition, as a mental disposition operating in implicit systems, is in close correlation with working memory. It infers quick, almost immediate meaning of un unknown word which appears in a context. Linguistic intuition has a regulatory function, i.e. it allows to continue language activities and overcome linguistic deficits. In the second part, Timed inference test as a tool for developing and testing vocabulary is proposed as well as the results of the empirical study on intuitive behaviour in L2. The results of the study show that inference of word’s meaning under time constraint is lower that the results of inference without time pressure. The study involves a group of 102 students of French as a foreign language at B1 level.